UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN DI SEKOLAH MENENGAH PERTAMA NEGERI 16 KOTA JAMBI - Fitriah, Aidatil; Hasanah, Neneng (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the efforts of Islamic Religious Education teachers in improving the Qur’an reading ability of seventh-grade students at State Junior High School 16 Jambi City, as well as the supporting and inhibiting factors in its implementation. The background of this research is based on the fact that there are still students who have not been able to read the Qur’an fluently in accordance with the rules of tajwid, makhārijul huruf, and reading fluency. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The data sources include Islamic Religious Education teachers, seventh-grade students, and school administrators. The results show that the efforts of Islamic Religious Education teachers to improve students’ Qur’an reading ability are carried out through habituation of Qur’an reading before lessons, the application of tilawah and tahsin methods, providing special guidance for students who are not yet fluent, and using interesting learning media. Supporting factors include support from the school, student motivation, and a religious school environment. Meanwhile, inhibiting factors consist of limited instructional time, differences in students’ basic abilities, and a lack of support from the family environment. Therefore, the role of Islamic Religious Education teachers is crucial in improving students’ Qur’an reading ability through appropriate and continuous learning strategies.